Signalling organizational commitment to employability through job advertisements: the communication of HRD practices to young inexperienced job seekers. Issue 1 (1st January 2020) - Moore, Katherine; Khan, Maria Hameed
ABSTRACT: In a time where young people across most industrialized countries are at high risk of unemployment, there is a growing need for organizations to commit to developing the employability of young, inexperienced and unqualified job seekers to ensure their future sustainable employment. The current study draws on the notion of employability as a mutual responsibility of both organizations and individuals, the Human Resource Development (HRD) practices that develop employability in employees, and signalling theory to investigate the extent to which organizations communicate their commitment to developing young people's employability via job advertisements. The key employability HRD practices were conceptualized as training, competency development, career development, mentoring, coaching and networking opportunities. Content analysis was used to identify the HRD practices that appeared in job advertisements for entry-level positions. Cross-tabulations determined the frequency of practices across job classifications and work types. The results showed that more than half of the job advertisements included at least one reference to a key HRD practice. The findings suggest that organizations are signalling a commitment to developing the human capital and career identity elements of employability and, to a lesser extent, social capital for young job seekers. The implications for HRD practitioners and future research directions are discussed.